2015
DOI: 10.2217/epi.15.47
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Enhancers are Highly Altered in Systemic Lupus Erythematosus

Abstract: Objective: Histone modifications set transcriptional competency and can perpetuate pathologic expression patterns. We defined systemic lupus erythematosus (SLE)-specific changes in H3K4me3 and K3K27me3, histone marks of gene activation and repression, respectively. Methods: We used ChIP-seq to define histone modifications in monocytes from SLE patients and controls. Results: Both promoters and enhancers exhibited significant changes in histone methylation in SLE. Regions with differential H3K4me3 in SLE were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Shi et al [38] have shown that both promoters and enhancers exhibit significant changes in monocytes from SLE patients when compared with healthy controls. In particular, differentially methylated regions in SLE were significantly enriched in potential interferon-related TFBS.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [38] have shown that both promoters and enhancers exhibit significant changes in monocytes from SLE patients when compared with healthy controls. In particular, differentially methylated regions in SLE were significantly enriched in potential interferon-related TFBS.…”
Section: Discussionmentioning
confidence: 99%
“…They were purified by elutriation and adherence and were more than 90% pure by flow cytometry. The SLE samples reported in Figure 1 were obtained as part of a previously reported study under a separate IRB-approved protocol [33, 34]. MonoMac6 cells were used as a monocyte cell line, and K562 was used as an early hematopoietic stem cell line.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…HEK293 cells were cultured in DMEM with 10% cosmic calf serum and were obtained from ATCC and thawed fresh for these experiments. The SLE patient RNA samples have been previously reported [3, 33], although these analyses are new. Transfection of cells was performed by electroporation with the Amaxa Cell Line Lonza Nucleofector Kit (Amaxa Biosystems, Gaithersburg, MD) or Lipofectamine 2000 (ThermoFisher, Waltham, MA).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be very interesting to study how changes in the epigenome associate with disease. It was recently shown that monocytes isolated from patients with systemic lupus erythematosus (SLE) show clear changes in their enhancer landscape and that these changes particularly occur in regions associated with interferon responses, a critical hallmark of the inflammatory profile in SLE and a target for intervention in this disease (115). It is expected that many research programs will focus on comprehensive mapping of the epigenome in human disease to better understand disease development and possibly to identify specific epigenetic markers for disease, disease stages, and effectiveness of interventions.…”
Section: Therapeutics and Future Perspectivesmentioning
confidence: 99%